Multisystem inflammatory syndrome associated with COVID-19 from the pediatric emergency physician's point of view (2020)
Objective Multisystem inflammatory syndrome in children (MIS-C) associated with coronavirus disease (COVID-19) is a rare and challenging diagnosis requiring early treatment. The diagnostic criteria involve clinical, laboratory, and complementary tests. This review aims to draw pediatrician attention to this diagnosis, suggesting early treatment strategies, and proposing a pediatric emergency care flowchart. Sources The PubMed/MEDLINE/WHO COVID-19 databases were reviewed for original and review articles, systematic reviews, meta-analyses, case series, and recommendations from medical societies and health organizations published through July 3, 2020. The reference lists of the selected articles were manually searched to identify any additional articles. Summary of the findings COVID-19 infection is less severe in children than in adults, but can present as MIS-C, even in patients without comorbidities. There is evidence of an exacerbated inflammatory response with potential systemic injury, and it may present with aspects similar to those of Kawasaki disease, toxic shock syndrome, and macrophage activation syndrome. MIS-C can develop weeks after COVID-19 infection, suggesting an immunomediated cause. The most frequent clinical manifestations include fever, gastrointestinal symptoms, rash, mucous membrane changes, and cardiac dysfunction. Elevated inflammatory markers, lymphopenia, and coagulopathy are common laboratory findings. Supportive treatment and early immunomodulation can control the intense inflammatory response and reduce complications and mortality. Conclusions MIS-C associated with COVID-19 is serious, rare, and potentially fatal. The emergency department pediatrician must recognize and treat it early using immunomodulatory strategies to reduce systemic injury. Further studies are needed to identify the disease pathogenesis and establish the most appropriate treatment.